A video locality based buffering mechanism for VoD systems - Sarper, Hasan; Aybay, Isik (IEEE-Inst Electrical Electronics Engineers Inc, 2007)
Client side buffering and peer-to-peer computing can considerably improve the performance of VoD systems. Earlier, a module called LCBBS was developed for clients on a LAN. A FIFO based buffering mechanism was used in LCBBS, considering the video locality concept. In this way, clients first check their own buffers, and then their peers' buffers before requesting segments from remote servers. In this study, a leading segments-based buffering mechanism is integrated(1) to the LCBBS client. The simulation results indicate that the performance of the resulting VoD system is improved further, especially in terms of startup latency. The effect of video popularity was also tested, assuming that in a real life environment, some videos are more popular than others. When popularity is considered in buffering decisions, simulation results show that typical video clips are displayed smoothly with small delays even when the display rate is three times faster than the download rate.
Keywords: video streaming; video on demand; client side; buffering; video popularity